Nursing ethics: the role of nurse in clinical experimentation - Robert, Elisabetta; Sinaccio, Graziella; Spagnolo, A. G. (Medicina e Morale, 1993)
The Authors analyze the ethical problems of nurses in activating and conducting clinical experimentation. Particular attention is given to request of consent, information, truth-telling, physician/nurse/patient relationship, collaboration with relatives, quality of life, ethics committees because they represent important bioethical matters for a criticai reflection. They have to be considered as delicate questions that nurses often can face in research and in hospital practice.